Pengaruh Relaksasi Otot Progresif Terhadap Penurunan Kadar Glukosa Darah: A Literature Reviev - Windi Astuti; Kiki Rizqi Ependi; Nandini Dian Ayu; Tika Emiliasari; Irna Karunia Min Allooh (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Introduction : Diabetes Mellitus (DM) is a metabolic disease which the number of incident increasing these years. The International Diabetes Federation (IDF) placed Indonesia in the top 7 in the world as the number of DM patient aged 20-79 years reached 8.5 million people in 2013. Based on RISKESDAS result in 2007, DM prevalence increase from 1,1% to 2,1% in 2013. Blood glucose can be controlled by controlled diet and stress management. Stress management can be done with Progressive Muscle Therapy (PMR) in the form of mind-body therapy in complementaru therapy. PMR is one of the non-pharmacologies therapy which believed can reduced blood glucose level. Method : Searching journal articles is done in electronic media. The database comes from several sources such as: Science Direct, Elsevier, ProQuest, and Google Scholar. The keywords used were